2020
DOI: 10.1073/pnas.2010484117
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Rev1 catalyze protein-template DNA synthesis

Abstract: During DNA replication, replicative DNA polymerases may encounter DNA lesions, which can stall replication forks. One way to prevent replication fork stalling is through the recruitment of specialized translesion synthesis (TLS) polymerases that have evolved to incorporate nucleotides opposite DNA lesions. Rev1 is a specialized TLS polymerase that bypasses abasic sites, as well as minor-groove and exocyclic guanine adducts. Lesion bypass is accomplished using a unique protein-template mechanism in which the te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…A recent time-lapse crystallographic study of yeast Rev1 found that the ejection of the template base preceded nucleotide binding and that the templating base remained extrahelical even after nucleotide incorporation ( 12 ). Hydrogen bonding between the backbone amides of M685/G686 in the G-loop of yeast Rev1 help keep the template base extrahelical.…”
Section: Discussionmentioning
confidence: 99%
“…A recent time-lapse crystallographic study of yeast Rev1 found that the ejection of the template base preceded nucleotide binding and that the templating base remained extrahelical even after nucleotide incorporation ( 12 ). Hydrogen bonding between the backbone amides of M685/G686 in the G-loop of yeast Rev1 help keep the template base extrahelical.…”
Section: Discussionmentioning
confidence: 99%
“…Slow PP i release in the absence of the next correct dNTP is an intrinsic property of PolC, as it does not depend on association with the β-clamp, nor does it depend on either the N-terminal or exonuclease domains of the polymerase ( 25 ). Steady-state analysis of two Y-family DNA polymerases suggest that PP i is hydrolyzed at the polymerase active site prior to release ( 43 , 44 ). However, this is clearly not a general phenomenon as PolC does not hydrolyze PP i to Pi on a timescale that is relevant to nucleotide incorporation ( Supplementary Figure S5A ).…”
Section: Discussionmentioning
confidence: 99%
“…S. cerevisiae and human Rev1 function as a dCMP transferase, incorporating strictly dCMP opposite abasic sites and dG-lesions ( Nelson et al, 1996 ; Lin et al, 1999 ; Masuda et al, 2001 ). dCMP transferase activity is instructed by Rev1’s conserved active site side chain arginine residue via a protein-templated mechanism ( Nair et al, 2005 ; Weaver et al, 2020 ). We hypothesized that the conservation of the functional arginine and Rev1 consensus sequence ( Figure 7A ) would make T. lanuginosis Rev1 a bonafide dCMP transferase.…”
Section: Resultsmentioning
confidence: 99%
“…The unique feature of eukaryotic Rev1 orthologs is their efficiency at bypassing both damaged guanines and abasic sites using a deoxycytidyl transferase mechanism that limits Rev1 to exclusively incorporate dC ( Nelson et al, 1996 ). This is achieved by displacing the DNA lesion from the active site entirely and instead using a protein sidechain (R324 in S. cerevisiae and R357 in H. sapiens ) as the “template” which base pairs solely with dC ( Nair et al, 2005 , 2011 ; Weaver et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%